Hubungan Manajemen Menu Makanan Bergizi Dengan Penghematan Budget Logistik Pondok Pesantren An Nawawi Al Bantani - Aisya Putri Salsabila; Aisyah Qonita Aziz (Antigen : Jurnal Kesehatan Masyarakat dan Ilmu Gizi, 2024)
Islamic boarding schools are institutions where students usually live in huts (dormitories) using classical and general books as teaching materials, as well as studying Islamic religious knowledge in detail and practicing them. This research uses a qualitative method where researchers get answers from sources who have been interviewed, located in one of the modern Islamic boarding schools in Bogor, namely the An-Nawawi Al-Bantani Modern Islamic Boarding School. This research aims to analyze the relationship between menu management and budget savings at the An Nawawi Al Bantani Islamic Boarding School and explain the factors that can influence menu management in an effort to save logistics budgets. An Nawawi Al Bantani Islamic boarding school implements a policy of cooperation with vendors or suppliers as well as checking market prices directly to ensure quality and prices are appropriate. Apart from that, the lodge also manages food waste well, reduces waste, and ensures that leftover food that is suitable for consumption is reused.